SAT0316 Routine Assessment of Patient Index Data 3 (Rapid3) is a Valid Index for Routine Care in Patients with Osteoarthritis - Lurati, A.; bompane, D.; marrazza, M.; Re, K. A.; scarpellini, M. (Annals of the rheumatic diseases, 2013)
Background RAPID3 (routine assessment of patient index data) is an arithmetic composite index of three Core Data Set, patient self-report, measures: physical function (0-3 converted to 0-10), pain (0-10), and patient global estimate (0-10) for a total of 0-30. It can be completed in the waiting room and can be calculated in only few seconds. Objectives Aim of this study was to compare RAPID3 with the Western Ontario and Mc-Master Universities Osteoarthritis Index (WOMAC) in patients with knee or hip osteoarthritis (OA) Methods patients with symptomatic knee or hip osteoarthritis as main rheumatologic diagnosis (VAS pain > 50 on a visual scale 0-100mm) according to the ACR (American College of Rheumatology) criteria and with stage 2 or 3 according to the Kellgren-Lawrence radiographic criteria were eligible. All subjects were clinically evaluated individually by an experienced rheumatologist and were asked to complete the self-report questionnaires (the original version of the WOMAC for hip or knee osteoarthritis and the RAPID3). There was no specific order in which the tests were completed; rather, each participant selected the order. Agreement between WOMAC and RAPID3 scores was estimated with rho Spearman correlation statistic. Cronbach’s alpha also was determined to evaluate the internal consistency of RAPID3 items Results 218 patients (63 males, 155 females) with hip (n=93) or knee (n=125) osteoarthritis were enrolled in daily practice clinical care during 2010-2012. Mean age (±SD) was 62±7.4 years old. Mean score was 58±8.1 for WOMAC and 7.2±1.5 for RAPID3. RAPID3 and WOMAC have shown a global correlation rho index of 0.78 (p<0.01) and a Cronbach’s alpha of 0.94. Computing analysis for diagnosis, the means of WOMAC and RAPID3 weren’t significantly different between patients with hip or knee osteoarthritis (62± 7.2 vs 63±3.8 and 6.2±2.6 vs 6.3±2.8, respectively. p>0.05). The Spearman’s rho was 0.78 for hip osteoarthritis (p<0.01) and 0.84 for knee osteoarthritis. Cronbach alpha was 0.91 for hip osteoarthritis (p< 0.01) and 0.85 for knee osteoarthritis, respectively Conclusions Up to date there’s not literature about the use of RAPID3 in patients with OA. In our study we found a strong correlation between RAPID3 and WOMAC in patients with either hip and knee OA. RAPID3 provide informative quantitative data for patient status from one visit to the next comparable to other self-reported questionnaire as WOMAC in a time sparing manner Disclosure of Interest None Declared